Adam Watkins' First Rocket Launch - Watkins, Howard::::::::: (1985)
Adam Watkins holding 12-inch rocket ready for launch in open lawn area at Jackson Elementary School Rocket launched 200-300 feet in air before parachute deployed; wind took it blocks away to unknown location